Sensitization to various minor house dust mite allergens is greater in patients with atopic dermatitis than in those with respiratory allergic disease. Issue 8 (11th June 2018) - Park, K. H.; Lee, J.; Lee, J.‐Y.; Lee, S. C.; Sim, D. W.; Shin, J. U.; Park, C. O.; Lee, J.‐H.; Lee, K. H.; Jeong, K. Y.; Park, J.‐W.
Summary: Background: Various allergenic proteins are produced by house dust mites (HDM). However, the allergenicity and clinical implications of these allergens are unknown. Objective: The purpose of this study was to identify allergens in Dermatophagoides farinae and elucidate the sensitization profiles to these in Korean patients suffering from respiratory (allergic rhinitis and/or asthma) and atopic dermatitis symptoms. Methods: IgE reactivities in sera from 160 HDM allergy patients were analysed by one‐ and two‐dimensional gel electrophoresis and immunoblotting. IgE‐reactive components were identified by liquid chromatography‐coupled electrospray ionization‐tandem mass spectrometry. Nine recombinant mite allergens (Der f 1, Der f 2, Der f 10, Der f 11, Der f 13, Der f 14, Der f 30, Der f 32 and Der f Alt a 10) were produced, and the IgE reactivity in sera to each was determined by ELISAs. Results: Der f 1 and Der f 2 were recognized by IgE in serum samples from 88.1% and 78.1% of all patients, respectively. Patients with respiratory allergies were mainly sensitized to these major allergens, whereas patients with atopic dermatitis symptoms showed polysensitization to major and minor allergen components (including Der f 11, Der f 13, Der f 14, Der f 32 and Der f Alt a 10). Conclusions: Patients with respiratory allergic disease sensitize to major allergen components of HDM. Those with atopic dermatitis were sensitized to a broader range of minor allergen components of HDM (Der f 11, Der f 13, Der f 14, Der f 32 and Der f Alt a 10).